Soluble guanylate cyclase stimulator BAY 41-8543 and female sex ameliorate uremic aortic remodeling in a rat model of mild uremia - Stancu, Bianca; Kraemer, Stephanie; Loof, Tanja; Mika, Alice; Amann, Kerstin Ute; Neumayer, Hans-H.; Peters, Harm (Journal of Hypertension, 2015)
Cardiovascular disease is the leading comorbidity in renal patients and has been related to impaired nitric oxide signaling. Estrogens exert protective effects on the vascular system. This study investigates the effects of biological sex and nitric oxide-independent soluble guanylate cyclase (sGC) stimulator BAY 41-8543 on aortic remodeling in experimental mild uremia.Age-matched male and female Wistar rats were assigned for 18 weeks into sham-operated, subtotally nephrectomized (SNX), SNX + BAY 41-8543 and SNX + hydralazine. Analysis involved functional, histological, and molecular kidney and thoracic aorta parameters.SNX significantly increased SBP, which was comparably reduced to control levels by BAY 41-8543 and hydralazine. In SNX males, uremic aortic remodeling was characterized by marked media thickening and increased media-to-lumen ratio (P < 0.01), vascular smooth muscle cell (VSMC) proliferation, macrophage infiltration, extracellular matrix turnover, decreased aortic elastin-to-collagen ratio (P < 0.01) and endothelial nitric oxide-synthase (eNOS) mRNA expression (P < 0.05). No significant alterations of aortic media-to-lumen ratio, VSMC proliferation, macrophage infiltration, matrix metalloproteinase-2, and eNOS mRNA expressions were seen in female uremic animals. BAY 41-8543 significantly ameliorated uremic aortic remodeling and stiffening involving reduced VSMC proliferation, collagen I-deposition, extracellular matrix turnover, and increased elastin content and eNOS mRNA expression. Hydralazine treatment did not substantially alter aortic remodeling.Experimental mild uremia leads to pronounced aortic hypertrophic remodeling and stiffening with sex-dependent alternations, and these are more severe in male rats. BAY 41-8543 ameliorates uremic aortic remodeling in a blood pressure-independent manner. The results suggest that sGC-stimulators may offer a novel treatment mode for pathological arterial wall remodeling in patients with impaired renal function.
EVALuna2:25503